Specificity of NHERF1 regulation of GPCR signaling and function in human airway smooth muscle. Issue 8 (1st May 2019) - Pera, Tonio; Tompkins, Eric; Katz, Michael; Wang, Bin; Deshpande, Deepak A.; Weinman, Edward J.; Penn, Raymond B.
ABSTRACT: Na + /H + exchanger regulatory factor 1 (NHERF1; also known as ezrin‐radixin‐moesin–binding phosphoprotein 50) is a PSD‐95, disc large, zona occludens‐1 adapter that acts as a scaffold for signaling complexes and cytoskeletal‐plasma membrane interactions. NHERF1 is crucial to β‐2‐adrenoceptor (β2 AR)‐mediated activation of cystic fibrosis transmembrane conductance regulator (CFTR) in epithelial cells, and NHERF1 has been proposed to mediate the recycling of internalized β2 AR back to the cell membrane. In the current study, we assessed the role of NHERF1 in regulating cAMP‐mediated signaling and immunomodulatory functions in airway smooth muscle (ASM). NHERF1 knockdown attenuated the induction of (protein kinase A) phospho–vasodilator‐stimulated phosphoprotein (p‐VASP) by isoproterenol (ISO), prostaglandin E2 (PGE2 ), or forskolin (FSK) as well as the induction of p‐heat shock protein 20 after 4 h of stimulation with ISO and FSK. NHERF1 knockdown fully abrogated the ISO‐, PGE2 ‐, and FSK‐induced IL‐6 gene expression and cytokine production without affecting cAMP‐mediated phosphodiesterase 4D (PDE4D) gene expression, phospho–cAMP response element–binding protein (p‐CREB), and cAMP response element (CRE)‐Luc, or PDGF‐induced cyclin D1 expression. Interestingly, NHERF1 knockdown prevented ISO‐induced chromatin‐binding of the transcription factor CCAAT‐enhancer–binding protein‐β (c/EBPβ). c/EBPβ knockdown almost completely abrogated the cAMP‐mediated IL‐6 but not PDE4D gene expression. The differential regulation of cAMP‐induced signaling and gene expression in our study indicates a role for NHERF1 in the compartmentalization of cAMP signaling in ASM.—Pera, T., Tompkins, E., Katz, M., Wang, B., Deshpande, D. A., Weinman, E. J., Penn, R. B. Specificity of NHERF1 regulation of GPCR signaling and function in human airway smooth muscle. FASEB J. 33, 9008–9016 (2019). www.fasebj.org